2012
DOI: 10.1002/bit.24494
|View full text |Cite
|
Sign up to set email alerts
|

Role of non‐specific DNA in reducing coding DNA requirement for transient gene expression with CHO and HEK‐293E cells

Abstract: Transient gene expression (TGE) is a rapid method for the production of recombinant proteins in mammalian cells. While the TGE volumetric productivity has improved significantly over the past decade, the amount of plasmid DNA (pDNA) needed for transfection remains very high. Here, we examined the use of non-specific (filler) DNA to partially replace the transgene-bearing plasmid DNA (coding pDNA) in transfections of Chinese hamster ovary (CHO) and human embryo kidney (HEK-293E) cells. When the optimal amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Filler plasmids are used to titrate the effector gene-encoding plasmid Rajendra et al, 2015Rajendra et al, , 2012, whereas promotors with different strengths drive transcription at different rates (Brown and James, 2015;Qin et al, 2010). The filler plasmid principle is a cost-efficient solution in transient expression-based setups, as no additional cloning work is needed besides a single plasmid preparation of the filler plasmid.…”
Section: Effector Gene Dosagementioning
confidence: 99%
See 2 more Smart Citations
“…Filler plasmids are used to titrate the effector gene-encoding plasmid Rajendra et al, 2015Rajendra et al, , 2012, whereas promotors with different strengths drive transcription at different rates (Brown and James, 2015;Qin et al, 2010). The filler plasmid principle is a cost-efficient solution in transient expression-based setups, as no additional cloning work is needed besides a single plasmid preparation of the filler plasmid.…”
Section: Effector Gene Dosagementioning
confidence: 99%
“…However, the lower protein yield achieved with TGE in CHO cells has historically been a major drawback compared to the substantially higher yields obtained with stable gene expression (SGE). Thus far, extensive efforts to improve TGE yields in CHO cells have been made by optimizing the culture environment (Galbraith et al, 2006;Ye et al, 2009), transfection efficiency (Mozley et al, 2014;Rajendra et al, 2015Rajendra et al, , 2012, vector systems (Cho et al, 2001;Mariati et al, 2010) and host cell line (Cain et al, 2013;Daramola et al, 2014;Macaraeg et al, 2013). Therefore, TGE has become a robust and flexible system, applicable to multiple r-proteins, expression volumes and bioprocesses with substantially increased yields of up to 3 g/L for MAbproducing CHO cells (Liu et al, 2015).…”
Section: Expression Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other groups have also reported similar observations. 9,10 These studies highlight the limitations of our current state of understanding of a complex process and the need for a more quantitative and detailed analysis of nanoparticle compositions. By enabling rapid DNA content distribution, our method will be an invaluable tool to accomplish this.…”
Section: Distribution Of Dna Content In Polyethylenimine (Pei)/dna Anmentioning
confidence: 99%
“…We have showed that the supplementation of plasmid DNA with non-coding DNA to increase extracellular DNA concentration, increases the transfection efficiency and TGE yield per unit plasmid 33 . Such an increase was shown to be accompanied by an increase in transgene mRNA levels 34 . After the initial delivery of plasmid to the cell, plasmid copy numbers continuously decrease due to dilution by cell division resulting in decrease in protein expression.…”
Section: Host Cells and Host Cell Engineeringmentioning
confidence: 94%